Penerapan IPA dalam Pembuatan Produk Inovatif: Menjawab Tantangan Industri - Mas’udah, Hikmah; Supardi (Zona Education Indonesia, 2025)
Natural Sciences (IPA) have a crucial role in encouraging innovation and increasing product competitiveness, especially in the small and medium industry (IKM) sector. This research aims to examine the application of science concepts in the process of innovation of IKM products, identify the challenges faced, and explore the potential for collaboration between academics and industry in strengthening the innovation ecosystem. The results of the study show that a number of SMEs have begun to integrate basic principles of chemistry, physics, and biology in the production process, which has an impact on improving product efficiency, quality, and sustainability. However, there are still significant obstacles, such as limited access to experts, laboratory facilities, and a lack of science-based training. These findings underscore the importance of policy support and synergy between the education sector, government, and industry to create an inclusive and sustainable science-based innovation ecosystem. With the right approach, the application of science in the SME sector can not only increase the competitiveness of local products, but also accelerate the transition to a knowledge-based economy